2012
DOI: 10.1038/emboj.2012.256
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization and direct membrane interaction of Nup53 contribute to nuclear pore complex assembly

Abstract: Nuclear pore formation depends on membrane curvature. The membrane deforming activity of Nup53 is required for nuclear pore complex (NPC) assembly during interphase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(157 citation statements)
references
References 63 publications
7
147
2
Order By: Relevance
“…5D). The inner ring is anchored to the pore membrane through membrane-binding motifs (MBMs) on the β-propellers at the N-termini of Nup157 and Nup170, and on the C-termini of Nup53 and Nup59 1719 . These proteins also interact with the scaffold-facing domains of Pom152, Ndc1, and Pom34, each of which carry transmembrane domains (TMDs) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5D). The inner ring is anchored to the pore membrane through membrane-binding motifs (MBMs) on the β-propellers at the N-termini of Nup157 and Nup170, and on the C-termini of Nup53 and Nup59 1719 . These proteins also interact with the scaffold-facing domains of Pom152, Ndc1, and Pom34, each of which carry transmembrane domains (TMDs) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NDC1 is also likely to be involved at this step (Mansfeld et al, 2006;Stavru et al, 2006) but its function is less defined. Components of the second major structural subunit of the NPC, the Nup93 complex, subsequently assemble stepwise from the membrane building laterally towards the centre of the NPC (Dultz et al, 2008;Sachdev et al, 2012;Vollmer et al, 2012), which allows for the recruitment of the central channel components, the FGnucleoporins. The final steps of NPC assembly are the addition of peripheral nucleoporins, which form extensions to the cytoplasmic and nucleoplasmic sides of the pore (Bodoor et al, 1999;Hase and Cordes, 2003;Dultz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other nucleoporins, such as Nup53 and Nup155 are also involved in NPC assembly into the nuclear envelope. Nup53, for instance, directly interacts with the nuclear envelope both in yeast and Xenopus (Marelli et al, 2001;Vollmer et al, 2012). In addition, several studies have identified interactions between Nup53 and transmembrane protein Ndc1 (Mansfeld et al, 2006;Onischenko et al, 2009;Eisenhardt et al, 2014;HawrylukGara et al, 2008).…”
Section: Roles Of Npcs and Linc Complexes In Nuclear Envelope Architementioning
confidence: 99%